Enhance the efficiency of [CeO2(NP)/Cu(NP)] PEC cell photoanode for hydrogen production by laser illumination - Sally A. Al-Ani; Mohamed K. Dhahir (Iraqi Journal of Laser, 2025)
This research introduces a novel approach to enhancing solar-to-hydrogen (STH) efficiency by applying laser illumination with the assistance of a UV source to illuminate the photoanode in photoelectrochemical (PEC) cells, representing a significant departure from conventional methods relying solely on solar light. The photoanode was fabricated using a (CeO₂ and Cu) nanoparticles thin film through the drop-casting method, the materials were chosen for their favorable optical and electronic properties, which are key in improving the hydrogen production rate. What sets this study apart is the innovative use of laser illumination, which allows for more precise and concentrated light absorption that match the materials’ absorption peaks compared to the broad spectrum of traditional sunlight. The structural properties of the materials were examined using X-Ray diffraction (XRD), (FE-SEM) to get the cross-sectional image and the optical properties were characterized by the UV-VIS-NIR spectrophotometer. Photoelectrochemical measurements were carried out by linear sweep voltammetry in the dark and under illumination condition AM 1.5 G of 100 mW/cm2.Our findings reveal that under laser and UV illumination, the PEC cell substantially improves photocurrent density and efficiency by 12.3%, outperforming traditional solar light irradiation with an efficiency of 5.5%. This work sets a new direction for PEC cell optimization by demonstrating the effectiveness of laser-assisted light in boosting hydrogen production, representing a significant step forward in renewable energy research.